2012
DOI: 10.1007/s11250-012-0167-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Streptococcus agalactiae and Streptococcus uberis isolates from bovine milk

Abstract: Streptococci are one among the major mastitis pathogens which have a considerable impact on cow health, milk quality, and productivity. The aim of the present study was to investigate the occurrence and virulence characteristics of streptococci from bovine milk and to assess the molecular epidemiology and population structure of the Indian isolates using multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). Out of a total of 209 bovine composite milk samples screened from four herds (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 37 publications
10
33
0
1
Order By: Relevance
“…Likewise, similar results were obtained for S. uberis isolated from mastitis samples in other geographic regions (KHAN et al, 2003;ROSEY et al, 1999;SHOME et al, 2012;LEIGH, 2004). Perrig et al (2015) related the presence of the pauA gene in 94.9% of the strains studied.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Likewise, similar results were obtained for S. uberis isolated from mastitis samples in other geographic regions (KHAN et al, 2003;ROSEY et al, 1999;SHOME et al, 2012;LEIGH, 2004). Perrig et al (2015) related the presence of the pauA gene in 94.9% of the strains studied.…”
Section: Resultssupporting
confidence: 75%
“…Perrig et al (2015) related the presence of the pauA gene in 94.9% of the strains studied. Other studies conducted in India showed that the prevalence of the pauA gene was 100% (KHAN et al, 2003;SHOME et al, 2012). In contrast, Reinoso et al (2011) showed a slower frequency (61.5%) of this gene in strains isolated from bovine mastitis samples in Argentina.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations